Simple, Selective, and Rapid Quantification of 1-Deoxynojirimycin in Mulberry Leaf Products by High-Performance Anion-Exchange Chromatography with Pulsed Amperometric Detection - Yoshihashi, Tadashi; Do, Huong Thi Thu; Tungtrakul, Patcharee; Boonbumrung, Sumitra; Yamaki, Kohji (Journal of food science, 2010)
1‐Deoxynojirimycin (DNJ) occurs in mulberry and other plants and is a highly potent glycosidase inhibitor reported to suppress blood glucose levels, thus preventing diabetes. Derivatization is required for quantification of DNJ upon use of spectral detection methods. Because of this difficulty, the DNJ contents of mulberry‐based food products are rarely stated, even if DNJ is their active component. A simple, selective, and rapid method of high‐performance anion‐exchange chromatography with pulsed amperometric detection (HPAEC‐PAD) to quantify DNJ in mulberry‐based food products was developed. Stability testing of DNJ under heat treatment was also performed. A water extract of mulberry tea sample was subjected to HPAEC‐PAD in a CarboPac MA1 column with a sodium hydroxide gradient. DNJ was clearly separated at a retention time of 7.26 min without interference and was selectively detected in the water extract. The detection limit was 5 ng. Heat stability studies suggested that DNJ was heat stable. HPAEC‐PAD was not subject to interference, was highly selective for DNJ, and was superior to other high‐performance liquid chromatography (HPLC) techniques in terms of sample preparation, resolution, and sensitivity. The method allowed simple, selective, and rapid analysis of DNJ in food matrices and might be useful for development of mulberry‐based food products. Heat treatment could be an option for sterilizing mulberry‐based products.